Laryngeal complications after thyroidectomy: is it always the surgeon? - Echternach, Matthias; Maurer, Christoph; Mencke, Thomas; Schilling, Martin; Verse, Thomas; Richter, Bernhard (Archives of surgery, 2009)
Laryngeal dysfunction after thyroidectomy is a common complication. However, few data are available to differentiate whether these complications result from injury to the recurrent nerve or to the vocal folds from intubation.University medical center.Seven hundred sixty-one patients who underwent surgery to the thyroid gland from 1990 to 2002. Of these patients, 8.4% underwent a revision thyroidectomy.Preoperative and postoperative laryngostroboscopic examination.Laryngostroboscopic evaluation of laryngeal complications.The overall rate of laryngeal complications was 42.0% (320 patients). Complications from an injury to the vocal folds occurred in 31.3% of patients. Weakness or paresis of the recurrent nerve was initially present in 6.6% and was related to the nerves at risk. This rate was higher in revision thyroidectomies than in primary surgical interventions (6.2% vs 11.6%; P = .04). The rate of laryngeal injuries was higher in patients older than 65 years (39.8% vs 30.8%; P = .03).These data suggest that laryngeal complications after thyroidectomies are primarily caused by injury to the vocal folds from intubation and to a lesser extent by injury to the laryngeal nerve. We recommend documentation of informed consent, especially for patients who use their voice professionally, such as singers, actors, or teachers.Arch Surg. 2009;144(2):149-153-->
Gesehen am 23.06.2022